Improvement of special physical training of athletes 9-10 years old engaged in rhythmic gymnastics - Deyneko, A.; Krasova, I. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to substantiate the effectiveness of using the author's methodology for improving the special physical training of athletes 9-10 years old engaged in artistic gymnastics.